Optimizing IT for Physical and Psychological Preparedness in Online Birthing Classes - Ella Nurlelawati; Kursih Sulastriningsih; Lilik Susilowati; Rosmiati Rosmiati (Universitas Raharja, 2024)
To face the labor process and get a positive experience during the labor process, it requires various preparations. Starting from knowledge, physical preparation and mental preparation. Breath is a vital source of life for living things, both humans, animals and plants. When a baby is born into the world, the first thing it does is breathe. When a mother in labor catches her breath, the mother will be able to control her mind and body so that the birth process that is experienced becomes smooth and minimally traumatized. The purpose of the study was to find out the effectiveness of breathing for birth with physical and psychological readiness in pregnant women in facing the birth process through online classes at Bidan Kita Klaten in 2022. The method of this research is quantitative research. The research design used was cross-sectional (cross-sectional). The sampling technique used was purposive sampling, with a sample of 122 pregnant women who took the online breathing for birth class at Bidan Kita Klaten. The results of the Pearson Correlation statistical test show that there is a relationship between online breathing for birth class learning and the mother's physical readiness to face childbirth (sig. (2-tailed) 0.000 (less than 0.05)). The correlation value is 0.956, meaning that the two variables have a strong or perfect relationship. The value of r = +1 means a perfect positive linear relationship. There is a relationship between online breathing for birth class learning and the psychological readiness of mothers in facing childbirth (sig. (2-tailed) 0.000 (less than 0.05)). The correlation value is 0.944, meaning that the two variables have a strong or perfect relationship. The value of r = +1 means a perfect positive linear relationship.